(untitled) (Experimental biology, 2024)
The purpose of the work is to assess the taxonomic diversity of the Ranunculaceae family in the Tobol-Ishim and Turgai floristic regions of Kazakhstan. The work is based on the results of field research (2018-2023), conducted using the traditional route reconnaissance method. Herbarium materials on this family stored in institutions were critically examined: Herbarium of the Institute of Botany and Phytointroduction, Almaty (AA), Herbarium of the Pedagogical Institute named after. U. Sultangazina, Kostanay (KSPI); MSU, Moscow (MW); Herbarium of Higher Plants of the Botanical Institute named after. V. L. Komarova (LE); Herbarium of the Institute of Plant and Animal Ecology, Yekaterinburg (SVER).